LITERARY ANALYSIS: THE IMPACT OF PRODUCT EXCELLENCE ON KENTUCKY FRIED CHICKEN (KFC) FAST FOOD RESTAURANT - Rahayu, Isyana; Lestari, Dheri Febiyani; Nurfadilah, Geni; Silalahi, Marto (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
Business expansion in this era of globalization is significantly on the rise, and competition is intense. One such example of a company that has been experiencing substantial growth is a culinary business operating primarily within the fastfood sector. Hence, it is imperative for enterprises to prioritize the caliber of their merchandise in order to deliver contentment to patrons and garner their loyalty, thereby augmenting their competitive edge. Prior researchs hold immense significance as they substantiate and reinforce forthcoming scientific theories. The aim of penning this literature review is to scrutinize product quality. The literature provides insights into the variables of product quality, service quality, customer satisfaction and customer loyalty. It also highlights that research methodologies such as SPSS and PLS are widely used. The outcomes indicate a positive correlation between product quality and factors like purchase decisions, customer satisfaction and loyalty.